DAMPAK SHARIA COMPLIANCE TERHADAP KEUNTUNGAN UMKM DIBANGKALAN - Eva Novia; Ahmad Musadad (PROCEEDING UMSURABAYA, 2022)
MSMEs have a significant role in economic development in Indonesia, namely by providing job opportunities and expanding job opportunities to the community. Since the outbreak of the COVID-19 disease in Indonesia has affected MSMEs in Indonesia, one of them is the problem of decreasing MSME results. Sharia compliance is a sharia compliance guideline used in an MSME activity by sharia rules and does not deviate from Islamic teachings. Profit results from product sales, which is an integral part of MSMEs. The research entitled the effect of sharia compliance on the profits of MSMEs in Bangkalan aims to find out how the implementation of sharia compliance in MSME activities is, how does sharia compliance affect the earnings of MSMEs in Bangkalan.In the preparation of this study using qualitative research methods with normative, descriptive research types, namely by describing the conditions in the research area and then connecting them with references from books and journals. To conduct this research using data collection techniques through observation, interviews and documentation.Keywords: Sharia compliance ; Profit; MSME